Some results of physical rehabilitation of victims with consequences of mine-blast injury of lower extremities - Дандаш, Хасан; Підкопай, Денис; Підкопай, Тетяна; Юсеф, Шарбель (Slobozhanskyi Herald of Science and Sport, 2018)
Hassan Dandash, Denis Podkopai, Tetiana Podkopai & Charbel Youssef Purpose: increase the effectiveness of physical rehabilitation of victims with the consequences of mine-explosive injury of the lower limbs at the polyclinic stage. Material & Methods: a study of the effectiveness of the physical rehabilitation of the victims with the consequences of the mine-explosive injury of the lower extremities at the polyclinic stage was carried out at the clinic of the Dorra-Center Medical Center in Belbek (state of Lebanon) on the basis of the physical rehabilitation department. Results: results of use in the study of the Minor sample, Schober’s test, and the modified S.D. Tumyan technique are presented and indicate the effectiveness of the proposed program of physical rehabilitation of victims after a mine explosion injury. Conclusion: the analysis of the results of the study showed that with positive dynamics of changes in the functional state of the victims of both clinical groups, the best results were obtained precisely from the victims of the main group who underwent physical rehabilitation according to the program proposed by us. In addition, in the affected main group at the same time and volume of observation, these indicators were better than the control group.